2017
DOI: 10.1007/s12185-016-2175-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of apoptosis-associated molecules in septic children with leukemia, neutropenia and fever

Abstract: It has been shown that Fas, Fas-L, TNF and TNFR-1 display high serum concentrations in subjects with sepsis. This suggests that these are potential severity markers. However, the serum concentration of these molecules in children with leukemia and suspected sepsis has to be established before proposing their use as diagnostic biomarkers. We included children <17 years of age diagnosed with acute lymphoblastic leukemia with neutropenia and fever (NF). The subjects were divided into two groups: (1) leukemia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Studies have shown that the increased apoptosis and rapid senescence of leukocytes are key processes in the pathophysiology of leukopenia. 5,6 It has also been extensively reported that mitochondrial damage is intimately associated with the formation of the apoptosomes and ultimately leads to neutrophil apoptosis. 7 Haematopoietic cell-specific protein 1-related protein X-1 (HAX-1), a prominent anti-apoptotic protein that is located predominantly in the mitochondria, is involved in the regulation of mitochondrial functions.…”
Section: What Is K Nown and Objec Tive Smentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the increased apoptosis and rapid senescence of leukocytes are key processes in the pathophysiology of leukopenia. 5,6 It has also been extensively reported that mitochondrial damage is intimately associated with the formation of the apoptosomes and ultimately leads to neutrophil apoptosis. 7 Haematopoietic cell-specific protein 1-related protein X-1 (HAX-1), a prominent anti-apoptotic protein that is located predominantly in the mitochondria, is involved in the regulation of mitochondrial functions.…”
Section: What Is K Nown and Objec Tive Smentioning
confidence: 99%
“…Studies have shown that the increased apoptosis and rapid senescence of leukocytes are key processes in the pathophysiology of leukopenia 5,6 . It has also been extensively reported that mitochondrial damage is intimately associated with the formation of the apoptosomes and ultimately leads to neutrophil apoptosis 7 .…”
Section: What Is Known and Objectivesmentioning
confidence: 99%
“…Previous studies have shown that increased apoptosis and rapid cell senescence of leukocytes underlined the pathophysiology of leukopenia. 5,6 Extensive studies have reported that mitochondrial damage was intimately associated with the formation of the apoptosome, and ultimately led to neutrophil cell apoptosis. 7 Hematopoietic cell-specific protein 1-related protein X-1 (HAX-1) is a prominent anti-apoptotic protein that is predominantly located in the mitochondria and is involved in the regulation of mitochondrial biological functions.…”
Section: What Is K Nown and Objec Tive Smentioning
confidence: 99%
“…Previous studies have shown that increased apoptosis and rapid cell senescence of leukocytes underlined the pathophysiology of leukopenia 5,6 . Extensive studies have reported that mitochondrial damage was intimately associated with the formation of the apoptosome, and ultimately led to neutrophil cell apoptosis 7 .…”
Section: What Is Known and Objectivesmentioning
confidence: 99%
“…The complexity of the acute phase reaction is illustrated by the observations from patients with febrile chemotherapy-induced neutropenia ( Table 1 ). Even these severely immunocompromised patients show an acute phase reaction with increased serum CRP levels in response to infections [ 10 ], and they also show significantly altered levels of a wide range of other mediators, especially regulators of inflammation as well as several other biomarkers [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. CRP is the only marker that is widely used in the routine clinical evaluation of these patients.…”
Section: The Acute Phase Reaction and The Biology Of Crpmentioning
confidence: 99%